1992
DOI: 10.2105/ajph.82.6.881
|View full text |Cite
|
Sign up to set email alerts
|

Health status of older male prisoners: a comprehensive survey.

Abstract: Although prison populations remain predominantly young, the number of older inmates in state and federal correctional facilities has been increasing. This report describes the results of a health survey of 119 male inmates 50 years of age and older residing in Iowa state correctional facilities. Subject's disease history included hypertension (40%), myocardial infarction (19%), and emphysema (18%). Most participants (97%) had missing teeth, 42% had gross physical functional impairments, and 70% smoked cigarett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
4
6

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(128 citation statements)
references
References 7 publications
(1 reference statement)
9
107
4
6
Order By: Relevance
“…These health problems were prominent in our study as well as hypertension, hypercholesterolemia, myocardial infarction, epilepsy, and diabetes, and are generally consistent with other findings involving older offenders (Colsher, Wallace, Loeffelholz, & Sales, 1992;Fazel, Hope, O'Donnell, Piper, & Jacoby, 2001;Hayes, Burns, Turnbull, & Shaw, 2012). In any event, 60.3% of the older offenders deemed criminally irresponsible in our study had experienced a problematic pattern of lifetime alcohol consumption.…”
Section: Health Characteristicssupporting
confidence: 92%
“…These health problems were prominent in our study as well as hypertension, hypercholesterolemia, myocardial infarction, epilepsy, and diabetes, and are generally consistent with other findings involving older offenders (Colsher, Wallace, Loeffelholz, & Sales, 1992;Fazel, Hope, O'Donnell, Piper, & Jacoby, 2001;Hayes, Burns, Turnbull, & Shaw, 2012). In any event, 60.3% of the older offenders deemed criminally irresponsible in our study had experienced a problematic pattern of lifetime alcohol consumption.…”
Section: Health Characteristicssupporting
confidence: 92%
“…Approximately 70% -80% of prisoners have been identifi ed as current smokers ( Belcher, Butler, Richmond, Wodak, & Wilhelm, 2006 ;Colsher, Wallace, Loeffelholz, & Sales, 1992 ;Conklin, Lincoln, & Tuthill, 2000 ;Cropsey, Eldridge, & Ladner, 2004 ;Cropsey, Eldridge, Weaver, Villalobos, & Stitzer, 2006 ;Cropsey & Kristeller, 2003, 2005Sieminska, Jassem, & Konopa, 2006 ). Consistent with previous population data, one study with female prisoners found prevalence rates of smoking to be higher for Whites than Blacks (79.5% vs. 71.3%; Cropsey et al, 2004 ) and found that Black female prisoners smoked fewer cigarettes per day than did White prisoners (11.1% vs. 19.2%;Cropsey et al, 2006 ).…”
Section: Original Investigationmentioning
confidence: 70%
“…The age constitutes an important factor. Older inmates report a lower level of general health compared to younger prison population [3,14,[63][64][65]. On the contrary, younger prisoners report lower self-reported mental health status in contrast to older inmates [66].…”
Section: Discussionmentioning
confidence: 95%